Lean Improvement To Reduce Usage Rate Of Production Supplies - Ko, Peck Yin (Universiti Sains Malaysia, 2017)
Production supplies are consumables used in production but have no direct connection to the product Bill of Material (BOM). A production requires varying quantities of heterogeneous production supplies and often independent regulating methods. Contemporary literature reveals production supplies management in industries often suffers from poor inventory records, multiple storage locations, uncoordinated purchasing, frequent out of stock conditions, and lack of managerial attention (Scheuing & Krauter, 2005). The manuscript presented a case study to reduce usage rate of production supplies in Quantum cell through Kaizen. The Kaizen followed Plan-Do-Check-Act (PDCA) methodology with focus prioritization on highly consumed production supplies. Lean tools were presented at different phases of PDCA to guide the group in decision making and implementation. Countermeasures were fully implemented and the usage rate was reduced as planned. The overall production supplies usage rate has reduced by 56.31% and the target has been achieved through those countermeasures. This case study offers a valuable reference and benchmark for Lean practitioners on similar usage rate reduction endeavors. Several issues highlighted could be worthwhile for operation management research. Keywords: PDCA, production supplies reduction, Kaizen and Lean tools.